A Shade Tolerant Forage, Stenotaphrum secundatum, in the Oil Palm Plantation to Support Cattle Productivity - Rijanto Hutasoit; R Rosartio; S Elisier; J Sirait; . Antonius; H Syawal (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2020)
The integration of livestock with plantations is one of efforts to support livestock agribusiness. The large potential  land area can be used for the development of cattle. However, the low production, nutrient content and digestibility of natural grasses in the plantation are still an obstacle to increase cattle productivity. Therefore, the development of shade tolerant of forages is  one of the strategies to improve the quality and production of forages in the plantation area. This paper aims to review the role of Stenotaphrum secundatum as a shade tolerant forage in oil palm plantations in supporting cattle productivity. Biomass production of Stenotaphrum secundatum obtained was relatively high at 42,209 kg DM/ha/yr in oil palm plantations aged 3.5 years, estimated to be able to accommodate cattle of 11.8 AU/ha. With a moderate composition of nutrition, it can improve cattle growth performance with an average body condition score of 3.8. The livestock integration system by developing S. secundatum in the oil palm plantation area has a positive effect because it can reduce fertilizer and weeding costs of 4 million IDR/ha/yr. The average production of fresh fruit bunches (FFB) reaching 19.5 tons/ha/yr. It can be concluded that the role of S. secundatum in  oil palm plantations can support cattle productivity and increase palm oil production.